The influence of competence and service quality on the performance of population and civil registration service employees in Brebes Regency - Furqon Imansyah; herayati herayati; Martinus Wahyu Puronomo (Institute of Computer Science (IOCS), 2023)
Performance is the realization of work carried out by employees as a basis for assessing work results. High employee performance will be directly proportional to the results of organizational development. Conversely, poor performance will have an impact on organizational development. The type of research used is quantitative method with a population of 80 employees of the population and civil registration office of Brebes Regency. Of the 80 employees who were used as respondents, namely 44 employees, to determine the effect of competence and service quality on employee performance, the multiple linear test method of data processing was used using SPSS 26. Based on the results of the study, it was concluded that competence did not have a significant effect on employee performance with a value of 1.786. Service quality has a positive and significant effect of 4,011. The results of the f test in the study (simultaneously) together between the variables of competence and service quality on employee performance amounted to 47.339. The regression model used is Y = 1.643 + 0.288 X1 + 0.765 X2.